SAFE, a new therapeutic intervention for families of children with autism: study protocol for a feasibility randomised controlled trial. Issue 5 (27th May 2019) - McKenzie, Rebecca; Dallos, Rudi; Stedmon, Jacqui; Hancocks, Helen; Vickery, Patricia Jane; Ewings, Paul; Barton, Andy; Vassallo, Tara; Myhill, Craig
Abstract : Introduction: Incidence of autistic traits, mental health problems, stress and poor coping is high among family members of children with autism. These problems are coupled with challenging behaviour among children with autism. Current treatment for these families is disjointed and costly. The need for whole family support is supported by the National Institute for Health and Care Excellence recommendations, developments regarding children's service provision, research and requests by families of children with autism. Despite evidence that family therapies can provide benefits to these families, efficacy has not been subject to a randomised controlled trial. Systemic Autism-related Family Enabling (SAFE) is a new family therapy intervention designed specifically for families of children with autism. We aim to establish the feasibility of running a fully powered randomised controlled trial to evaluate SAFE. Methods and analysis: Families of children with autism aged 3–16 years will be invited to participate. Consenting participants will be randomised 2:1 to either SAFE+support as usual or support as usual alone. The proposed primary outcome measure for the main trial will be the Systemic CORE 15. Participants will also complete proposed secondary outcome measures, indexing changes in child behaviour, child-parent attachment, anxiety and depression. Generic health economic outcome measures (EuroQol 5 dimensions and Child Health Utility 9 Dimensions) will also provide data on the feasibility of cost-effectiveness analysis. Questionnaires will be completed at baseline and 32 weeks post-allocation. Data on ability to identify, recruit, randomise, retain and collect data from families, acceptability of outcome measures, adherence of therapists and families to the intervention, appropriateness of resource use questionnaires and effectiveness of training will be collected for feasibility analysis. Qualitative data will also explore acceptability of SAFE and reasons for declining and withdrawing from the study. Ethics and dissemination: The current trial protocol received ethical approval from the South West-Exeter Research Ethics Committee (Ref: 17/SW/0192). The findings of the trial will be disseminated in collaboration with our Family Consultation Group and other partners. Findings will be shared locally, nationally and internationally through events, conferences and published papers. Trial registration number: ISCTRN83964946 (Pre-results) IRAS 213527